Cartographies of the Gaze of the Other/Other Gazes: Youth, Slums, and Audiovisual Production in the Post-Media Age (Praxis Educativa, 2021)
Is there an specific gaze (to the) other? If so, what is it like? On the basis of audiovisual work produced during over ten years by young people who live in the urban slums of the Buenos Aires, we will attempt to address that which we call cartographies of gazes other. Who is the other when the narrator is the one usuallypositioned as the other? A word, a gaze, and it’s display emerge from lived experience, from the possibility of narrating that experience: the other through the other. If, as Guattari (1986) argues, subjectivity is the problem of any political system in contemporary societies, we will propose a schizo cartography as a means toapproach what is singular in the act of looking, an image-thought that can delineate something like a radicalization of the other gaze in the postmedia era. An era that fluctuates between infantilization, indifference, and generalized equivalence, on the one hand, and, on the other, the possibility of singularity and phrases uttered in the most ordinary situations, the possibility of embracing otherness without reservation.
Keywords: postmedia era; schizo cartography; gaze other; young people; urban poverty